2016
DOI: 10.1055/s-0042-113184
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Potential of Hecogenin in Experimental Animals: Possible Involvement of Inflammatory Cytokines and Myeloperoxidase

Abstract: Hecogenin is a steroidal sapogenin plays important role in treatment of variety of inflammatory diseases. We have investigated the anti-inflammatory effects of Hecogenin (50 µg/animal) (HG), Fluticasone (50 µg/animal) (FC) and Hecogenin+Fluticasone (HG+FC) combination (25 µg/animal, each) on various inflammatory models. The anti-inflammatory effect of HG, FC and HG+FC combination was studied on % inhibition of dry weight of granuloma tissue, Δ ear weight, myeloperoxidase assay, serum pro-inflammatory cytokines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 74 publications
1
6
0
Order By: Relevance
“…Further, it also suppressed the myeloperoxidase and serum levels of Tumour necrosis factor-α (TNF-α) and Interleukin-6 (IL-6) in cotton pellets induced granuloma model in rat. The result was further supported by histopathological analysis of ear tissue that showed significant decrease in dermal thickness and epidermal hyperplasia of ear tissue thus confirming its anti-inflammatory activity [16] ( fig. 3).…”
Section: Anti-inflammatory Role Of Hecogeninsupporting
confidence: 53%
See 1 more Smart Citation
“…Further, it also suppressed the myeloperoxidase and serum levels of Tumour necrosis factor-α (TNF-α) and Interleukin-6 (IL-6) in cotton pellets induced granuloma model in rat. The result was further supported by histopathological analysis of ear tissue that showed significant decrease in dermal thickness and epidermal hyperplasia of ear tissue thus confirming its anti-inflammatory activity [16] ( fig. 3).…”
Section: Anti-inflammatory Role Of Hecogeninsupporting
confidence: 53%
“…In addition to this, hecogenin exhibits variety of important biological activities in the pharmaceutical industry [12,13]. The steroidal sapogenins (hecogenin) from Agave genus were reported to have a number of pharmacological activities such as anti-inflammatory, analgesic, antiarthritis, gastroprotective, anticancer and larvicidal activity [14][15][16][17][18]. Overall, the results of numerous pharmacological studies have been linking the possible use of hecogenin as a novel multi-target based therapeutic agent against abundant long-lasting disease conditions.…”
Section: International Journal Of Pharmacy and Pharmaceutical Sciencesmentioning
confidence: 99%
“…Although the two aforementioned drugs have been reported to be associated with the treatment of ICH, the mechanisms underlying their therapeutic actions still require further research. In addition, we found that hecogenin has an anti-inflammatory effect that may contribute to the treatment of ICH (Ingawale, Mandlik & Patel, 2019; Ingawale & Patel, 2016; Ingawale & Patel, 2018).…”
Section: Discussionmentioning
confidence: 88%
“…Although the two aforementioned drugs have been reported to be associated with the treatment of ICH, the mechanisms underlying their therapeutic actions still require further research. In addition, we found that hecogenin has an antiinflammatory effect that may contribute to the treatment of ICH (Ingawale et al 2019;Ingawale & Patel 2016;Ingawale & Patel 2018).…”
Section: Discussionmentioning
confidence: 99%